Energy capture selection for interference reduction in high-data-rate impulse radio ultra wideband - Tjhi, Wilson Chandra (2012)
Impulse Radio Ultra Wideband (IR-UWB) promises a wireless communication system that is simple, yet capable of achieving a high data rate transmission. The wide bandwidth of the system implies that it has a large channel capacity. However achieving full utilization of this large channel capacity, while keeping the complexity of the system low, remains a practical challenge. This is mainly caused by the presence of Inter-Symbol Interference (ISI) in the high data rate transmission. Despite this, in many system analyses of IR-UWB system, the effect of ISI is often neglected. Most of the time, it is generally assumed that the symbol period is longer than the channel excess delay. This assumption is not valid in situations where data rate is high. The efforts to mitigate the ISI are mainly in the form of the classical equalization techniques. Another variant of UWB system, the WiMedia, avoids the ISI through the use of Multiband Orthogonal Frequency Division Multiplexing (OFDM). These two approaches increase the overall complexity of the system. The objectives of this research are to investigate the performance of high data rate IR-UWB and to develop good ISI reduction techniques, while keeping the simplicity of the system. In this thesis, the mathematical derivation of the IR-UWB receiver's test statistic under high data rate system is presented. From the mathematical derivation, a complete separation between the desired energy and the undesired energy that make up the test statistic of the detection system can be clearly observed. Based on this observation, two novel techniques based on selective energy capture are developed. The first technique reduces the interference from other symbols through the implementation of pulse shape hopping in the transmitter. By modifying the pulse shapes transmitted at every transmission instant, the pulse shape hopping technique reduces the cross-correlation value between pulses from different symbols. The improvement of the error rate performance is shown to be good and scalable, especially when orthogonal pulse shapes are used. The second technique introduces a correlation window selection, which is performed at the receiver. Through the use of the proposed selective transmitted reference technique, the receiver focuses the energy capture on the time period where the desired energy is stronger. The proposed selective transmitted reference technique outperforms other similar techniques presented in the literatures.